A functional role for Serum Amyloid A in the molecular regulation of autophagy in breast cancer - Manisha du Plessis; Tanja Andrea Davis; Daniel Wilhelm Olivier; Willem Johan Simon de Villiers; Anna-Mart Engelbrecht; Anna-Mart Engelbrecht (Frontiers in Oncology, 2022)
It has been established that the acute phase protein, Serum amyloid A (SAA), which is usually synthesized by the liver, is also synthesized by cancer cells and cancer-associated cells in the tumor microenvironment. SAA also activates modulators of autophagy, such as the PI3K/Akt and MAPK signaling pathways. However, the role of SAA in autophagy in breast cancer still remains to be elucidated. The aim of this study was to investigate the role of SAA in the regulation of signaling pathways and autophagy in in vitro and in vivo models of breast cancer. The MDA-MB-231 and MCF7 cell lines were transiently transfected to overexpress SAA1. A tumor-bearing SAA1/2 knockout mouse model was also utilized in this study. SAA1 overexpression activated ERK signaling in the MDA-MB-231 cells, downregulated the PI3K pathway protein, PKB/Akt, in the MCF7 cell line, while SAA1/2 knockout also inhibited Akt. Furthermore, SAA1 overexpression in vitro downregulated autophagy, while the expression of SQSTM1/p62 was increased in the MCF7 cells, and SAA1/2 knockout induced autophagy in vivo. SAA overexpression in the MDA-MB-231 and MCF7 cells resulted in an increase in cell viability and increased the expression of the proliferation marker, MCM2, in the MCF7 cells. Furthermore, knockout of SAA1/2 resulted in an altered inflammatory profile, evident in the decrease of plasma IL-1β, IL-6 and IL-10, while increasing the plasma levels of MCP-1 and TNF-α. Lastly, SAA1/2 knockout promoted resistance to apoptosis and necrosis through the regulation of autophagy. SAA thus regulates autophagy in breast cancer cells to promote tumorigenesis.